An Adaptive Pseudospectral Method for Constrained Dynamic Optimization Problems in Chemical Engineering. Issue 10 (5th September 2016) - Xiao, Long; Liu, Xinggao; He, Shiming
Abstract: An adaptive pseudospectral method with two novel strategies is proposed to solve constrained dynamic optimization problems in chemical engineering. The first strategy is to introduce slope information in designing appropriate subintervals, so that the approach becomes more efficient to track the optimal control profiles. The second strategy is to redistribute the collocation points based on the approximation error, thus ensuring the accuracy of the method. Two constrained dynamic optimization problems with multiple control variables are tested as illustrations, and the proposed approach is compared with other methods. The research results reveal the effectiveness of the proposed method in improving the solution accuracy of dynamic optimization problems. Abstract : An adaptive pseudospectral method for constrained dynamic optimization problems is presented. To overcome limitations of the classical pseudospectral method, the proposed approach allows the division of the time interval and the number of collocation points in each subinterval to vary. The method proved to be efficient in enhancing the solution accuracy of dynamic optimization problems.